2021
DOI: 10.3390/cells10112965
|View full text |Cite
|
Sign up to set email alerts
|

The Unfolded Protein Response as a Guardian of the Secretory Pathway

Abstract: The endoplasmic reticulum (ER) is the major site of membrane biogenesis in most eukaryotic cells. As the entry point to the secretory pathway, it handles more than 10,000 different secretory and membrane proteins. The insertion of proteins into the membrane, their folding, and ER exit are affected by the lipid composition of the ER membrane and its collective membrane stiffness. The ER is also a hotspot of lipid biosynthesis including sterols, glycerophospholipids, ceramides and neural storage lipids. The unfo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 204 publications
0
21
0
Order By: Relevance
“…When aggregation of misfolded proteins in the ER lumen occurs, UPR sensors detect the lesion and trigger the dissociation from Grp78. These alterations lead to the homo-dimerization and homo-oligomerization of IRE1α and PERK, respectively, and the migration of ATF6 to the Golgi apparatus, which induce the sophisticated downstream network of events [ 22 ]. The three pathways are artificially defined, and indeed a cross-interactive cascade modulating comprehensive cell responses to achieve adaption, or result in apoptosis ( Figure 1 ).…”
Section: Ers and Drug-resistance Of MMmentioning
confidence: 99%
“…When aggregation of misfolded proteins in the ER lumen occurs, UPR sensors detect the lesion and trigger the dissociation from Grp78. These alterations lead to the homo-dimerization and homo-oligomerization of IRE1α and PERK, respectively, and the migration of ATF6 to the Golgi apparatus, which induce the sophisticated downstream network of events [ 22 ]. The three pathways are artificially defined, and indeed a cross-interactive cascade modulating comprehensive cell responses to achieve adaption, or result in apoptosis ( Figure 1 ).…”
Section: Ers and Drug-resistance Of MMmentioning
confidence: 99%
“…LAMP2A is the rate-limiting step of CMA, as HSP70 threads the unfolded protein through its pore, into the lumen. The AKT/mTOR system regulates the phosphorylation/deactivation status of LAMP2A, increasing the stress status selectivity of Bag3–HSP70-mediated autophagy [ 85 ]. Unique to chaperone-mediated autophagy, the conditions of the docking receptor LAMP2A, the protein sequence K–F–E–R–Q (or KFERQ-like domain), and a loosely folded protein must be present for HSP70 to release the client to the lysosome.…”
Section: Protein Quality Controlmentioning
confidence: 99%
“…Regorafenib, a medication approved for colorectal cancer treatment, has been observed to indirectly obstruct autophagolysosome fusion. Successfully halting macroautophagy, teams have found that regorafenib induces apoptosis in recurrent and treatment-resistant glioblastoma multiforme [ 85 , 148 ].…”
Section: Glioblastoma As a Proteinopathymentioning
confidence: 99%
“…ER stress is sensed by a sophisticated system of transmembrane proteins, the inositol requiring enzyme 1α (IRE1α), protein kinase RNA-like endoplasmic reticulum kinase (PERK), and activating transcription factor 6 (ATF6), which are silenced by their binding to immunoglobin binding protein (BiP), which is the ER-resident heat shock 70 protein (Hsp70) protein. Vice versa, the activation of IRE1α, PERK, and ATF6 is induced by the release of BiP from their luminal domains and even by the direct binding of misfolded proteins to the luminal domains, as has been shown for IRE1α [ 1 , 2 , 3 , 4 ]. The activation of these proteins induces different pathways of a cell’s stress response, termed the unfolded protein response (UPR).…”
Section: Introductionmentioning
confidence: 99%